Vulnerability of an arid zone coastal wetland landscape to sea level rise and intense storms. Issue 11 (22nd September 2021) - Lovelock, Catherine E.; Reef, Ruth; Masqué, Pere
Abstract: Arid zone coastal wetlands provide disproportionally important ecosystem services due to their relatively high levels of productivity relative to adjacent terrestrial systems. However, these wetlands are vulnerable to sea level rise as sediments needed for vertical accretion are limited. In order to assess the processes important for vertical accretion in arid zone coastal wetlands, we assessed vertical accretion across an arid zone wetland landscape in Western Australia. We found that overall coastal wetlands were declining in elevation at −0.18 mm yr −1 (± standard error 0.12 mm yr −1 ). Vertical accretion in mangroves was evident in years of high mean sea level, but this was insufficient to counteract shallow subsidence. The high intertidal cyanobacterial mat and salt flat zones were eroding, particularly in years of high rainfall. We observed retreat of the seaward mangrove fringe associated with tree mortality caused by cyclones, but we also observed recruitment of mangroves onto the high intertidal cyanobacterial mat zone, attributed to higher sea levels. Our study found complexity in the factors causing landscape change across the intertidal zone, where variation in sea level, intense storms, and other climatic and biotic factors interact.